2022
DOI: 10.3390/en15218218
|View full text |Cite
|
Sign up to set email alerts
|

Electric Vehicles and Vehicle–Grid Interaction in the Turkish Electricity System

Abstract: Electric vehicles and energy storage systems are technologies in the stage of intensive development. One of the innovative ways to use electric cars is the Vehicle to Grid (V2G) concept. V2G charging points are characterized by the ability of bidirectional energy flow while charging EV/BEV (Electric Vehicles/Battery Electric Vehicles). In periods of low energy consumption and the presence of the highest shares of renewable sources, the cleanest electricity is drawn from the grid at the lowest prices and stored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…3, 2022 innovation system at an enterprise (Szostek, 2021;Bogachov et al, 2020;Borodin et al, 2021). The authors (Celma et al, 2012;Husnain et al, 2020;Chygryn et al, 2018;Coban et al, 2022a; found that corporate social irresponsibility is a powerful factor that negatively affects consumer loyalty and brand value in general (Oláh et al, 2021;Stuss et al, 2019;Vaníčková & Szczepańska-Woszczyna, 2020;Wróblewski et al, 2018), while the scientific community considers the possibility of a positive impact of corporate social responsibility in the management of labour resources for the image (Dacko-Pikiewicz, 2019;Dzwigol, 2020b;Dzwigol-Barosz & Dzwigol, 2021;Dzwigol et al, 2020b), corporate sustainability and reputation of a company (Advantage, 2020;Balaraman, 2017;Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…3, 2022 innovation system at an enterprise (Szostek, 2021;Bogachov et al, 2020;Borodin et al, 2021). The authors (Celma et al, 2012;Husnain et al, 2020;Chygryn et al, 2018;Coban et al, 2022a; found that corporate social irresponsibility is a powerful factor that negatively affects consumer loyalty and brand value in general (Oláh et al, 2021;Stuss et al, 2019;Vaníčková & Szczepańska-Woszczyna, 2020;Wróblewski et al, 2018), while the scientific community considers the possibility of a positive impact of corporate social responsibility in the management of labour resources for the image (Dacko-Pikiewicz, 2019;Dzwigol, 2020b;Dzwigol-Barosz & Dzwigol, 2021;Dzwigol et al, 2020b), corporate sustainability and reputation of a company (Advantage, 2020;Balaraman, 2017;Yang et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is justified by the reorientation of word development considering sustainable development principals (Abazov, 2021;Dźwigol et al, 2019;Kharazishvili et al, 2020). It requires the affordable investment (Miskiewicz, 2022;Melnychenko, 2021), knowledge, and innovation (Coban et al, 2022;Drożdż et al, 2020a;Ingber, 2017). At the same time, the logistic management should allow declining using of all recourses' types (Kharazishvili et al, 2021;Drożdż & Mróz-Malik, 2017) and reducing carbon dioxide emissions (Drożdż et al, 2021;Kotowicz et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…5, No. 2, 2022 infrastructure and green marketing (Lyonov et al 2021;Tambovceva et al 2020;Panchenko et al 2021;Letunovska et al 2021;Yang et al 2021); unlocking the economic potential (Abazov 1997(Abazov , 2010Dźwigoł & Wolniak, 2018;Miśkiewicz 2018Miśkiewicz , 2019Miśkiewicz , 2020Miśkiewicz , 2021aMiśkiewicz , 2021b; functioning and elaborating energy systems (Coban et al 2022;Miskiewicz et al 2021Miskiewicz et al , 2022Moskalenko et al 2022aMoskalenko et al , 2022b; energy and social security (Kharazishvili et al 2020(Kharazishvili et al , 2021Kotowicz et al 2022;Hezam et al 2023;Hussainet al 2021;Miskiewicz et al 2021Miskiewicz et al , 2022Prokopenko and Miśkiewicz 2020;Saługa 2020Saługa , 2021; development of information systems (Bogachov et al 2020;Borodin et al 2021;Drożdż et al 2020aDrożdż et al , 2020bDrożdż et al , 2021Dzwigol ,2021Dzwigol , 2022Dźwigol et al 2019Dźwigol et al , 2020Melnychenko 2020Melnychenko , 2021aMelnychenko , 2021b; determination of bifurcation points (Ingber 2017;Kianpour et al 2021;Kwi...…”
Section: Literature Reviewmentioning
confidence: 99%